Design and development of an impeller wind turbine - Ahmed Younus, Qasim
In the area of wind turbine design, there is still scope of improvement. Today, wind energy - mainly by wind screw turbines - produces less than 1.0% of the total energy used worldwide. Practically, the efficiency of the standard three-blade wind screw turbines is around 30%. This type of turbine is based on the wind lift force on rotating turbine. These turbines are quite expensive due to the complex aerodynamic shape of blades that are made of composite materials. A vertical axis wind turbine can be designed with high value of the drag factor. The present work relates to the design of a new impeller type vertical axis wind turbine, which is uses wind energy more effectively. This design presents a special frame design with vanes. The frame wind turbine is designed to increase the output of a wind turbine that uses kinetic energy of the wind. Five different models of the vertical axis wind turbine are fabricated and tested in a wind tunnel in the present work. They are three frame movable vane cavity shape, three frame movable vane cavity shape with amplifier gear, three frame fixed vane cavity shape, four frame movable vane cavity shape and three frame movable vane flat plate shape. The vanes are located on vertical bars installed in hinges of the frames. Such a design enables the rotation of the bars with frames under the action of wind force simultaneously at one direction and independently at other directions. The frames are connected with the shaft, of which one end is connected with the electric generator. The frames are designed with angular inclinations of vanes that create cavities when vanes are closed. On the other side of the impeller, when the movable vanes are open, and the frame is under wind action, the air passes freely through the frame, and decreases the negative torque. In all the models using cavity shaped vanes, 45˚vane angle is used.The results are presented in the form of drag coefficient, power coefficient, tip speed ratio for wind velocities varying from 5 m/sec to 17 m/sec. It is found that a three-frame movable vane cavity shape model has a maximum power coefficient (Cpmax) of 0.32 at a wind velocity 8 m/s and tip speed ratio 0.31. All other models give the values of Cpmax lower than this value for the same range of wind velocity. The proposed new impeller type vertical axis wind turbine can be used worldwide due to its high efficiency, simple construction, and simple technology. Further, the proposed wind turbine can also be made from cheap materials.